UPAYA PENINGKATAN AKTIVITAS SISWA SMKN 1 DEWANTARA DALAM PEMBELAJARAN PAI DENGAN MODEL KOOPERATIF JIGSAW - SAID MARZUKI (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2023)
This study aims to determine the increase in student activity in PAI learning through the jigsaw cooperative model for students of SMK Negeri 1 Dewantara. The method used in this research is a class action research method (CAR). Data collection techniques through interviews, observation, tests, documentation and data were analyzed descriptively. This research was conducted in 3 cycles, namely pre-cycle, cycle I and cycle II. The research subjects were 30 class XII OP students at SMKN 1 Dewantara for the 2020/2021 academic year. The results of research using the cooperative jigsaw model were able to increase student learning activities. This can be seen by researchers from several things as follows; Students can take part in the learning process more enthusiastically and enthusiastically, the emergence of students' courage in conveying ideas or thoughts, growing students' self-confidence in expressing their opinions, increasing students' sense of responsibility in participating in learning, very few students roaming around and disturbing friends. If it is calculated that students' activeness in cycle I was only 42.78% active, in cycle II student activity increased to 74.45%. Means an increase of 31.67%. Thus it means that the Jigsaw cooperative learning model is very suitable to be applied in the learning process of Islamic Religious Education at SMK Negeri 1 Dewantara, North Aceh Regency. ABSTRAKPenelitian ini bertujuan mengetahui peningkatan aktivitas siswa dalam pembelajaran PAI melalui model kooperatif jigsaw untuk siswa SMK Negeri 1 Dewantara. Metode yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas (PTK). Teknik pengumpulan data melalui wawancara, observasi, tes, dokumentasi dan data dianalisis secara deskriptif. Penelitian ini dilakukan dalam 3 siklus yaitu prasiklus, siklus I dan siklus II. Subjek penelitian adalah 30 orang siswa kelas XII OP SMKN 1 Dewantara tahun pelajaran 2020/2021. Hasil penelitian dengan menggunakan model kooperatif jigsaw ternyata dapat meningkatkan aktivitas belajar siswa. Ini dapat peneliti lihat dari beberapa hal sebagai berikut; Siswa dapat mengikuti proses pembelajaran lebih bergairah dan bersemangat, Timbulnya keberanian siswa dalam menyampaikan ide atau pikiran, Tumbuhnya rasa percaya diri siswa dalam mengemukakan pendapatnya, Meningkatnya rasa tanggungjawab siswa dalam mengikuti pembelajaran, Sangat kurang sekali siswa yang berkeliaran dan maupun mengganggu teman. Jika di kalkulasikan keaktifan siswa pada siklus I hanya 42,78 % saja yang aktif, pada siklus II aktivitas siswa meningkat menjadi 74,45 %. Berarti terjadi peningkatan 31,67 %. Dengan demikian berarti model pembelajaran kooparatif Jigsaw sangat cocok diterapkan dalam proses pembelajaran Pendidikan Agama Islam di SMK Negeri 1 Dewantara Kabupaten Aceh Utara.